A Preliminary Study to Tailor Planting Stock Suitable to Sodic Soils - Garg, V. K. (Indian Forester, 1998)
Seedlings of Acacia farnesiana, Acacia nilotica ssp. Cupressiformis and Prosopisjuliflora were raised in five types of growth mediums viz sand, sodic soil, sodic soil + sand, sodic soil + sand + pyrite, sodic soil + sand + peat-moss to overcome the problem of scanty root formation while planting them into the field or container in sodic soil. Results showed that the mixture of sodic soil + sand + peatmoss produced seedlings with a brush type root phenology compared to those grown in sodic soil. Such seedlings produced were not only taller but had a decreased root: shoot ratio also, thus better in quality.